Effect of static knee joint flexion on vastus medialis obliquus fiber angle in patellofemoral pain syndrome: An ultrasonographic study. Issue 7 (23rd July 2021) - Doğan, Ali; Şengül, İlker and Aşkın, Ayhan and Tosun, Aliye
Abstract: Introduction: In patients with patellofemoral pain syndrome, the vastus medialis obliquus muscle fiber angle measured by ultrasound at knee extension was found to be different from that in healthy individuals. An important feature of patellofemoral pain syndrome is the increase in pain severity during activities that require knee flexion. Objective: To investigate whether there was an ultrasonographic change in the vastus medialis obliquus fiber angle by flexing the knee joint in patients with patellofemoral pain syndrome compared to healthy pain‐free individuals. Design: A cross‐sectional clinical study. Setting: An outpatient clinic of a tertiary care hospital. Participants: Forty‐seven patients with patellofemoral pain syndrome (median age of 40 years) and 43 healthy volunteers (median age of 39 years) were included in the study. Interventions: No intervention. Main Outcome Measures: Vastus medialis obliquus fiber angle measured by ultrasonography at three different positions of knee joint including extension, 30° of flexion, and 45° of flexion. Results: There was no significant change in the vastus medialis obliquus fiber angle with knee flexion in both groups ( p > .05 for each group). However, the median vastus medialis obliquus fiber angle values in the group with patellofemoral pain syndrome were significantly lower at all knee joint angles than those in the comparison group ( p < .05 at all knee joint angles). Conclusions: Although the vastus medialis obliquus fiber angle does not change with static knee flexion, the lower angle of the vastus medialis obliquus fiber in those with patellofemoral pain syndrome implicitly suggests that vastus medialis obliquus dysfunction may exist.